2019
DOI: 10.1088/1674-1056/28/2/028501
|View full text |Cite
|
Sign up to set email alerts
|

Transition of photoconductive and photovoltaic operation modes in amorphous Ga 2 O 3 -based solar-blind detectors tuned by oxygen vacancies

Abstract: We report on the transition of photovoltaic and photoconductive operation modes of the amorphous Ga 2 O 3 -based solar-blind photodetectors in metal-semiconductor-metal (MSM) configurations. The conversion from Ohmic to Schottky contacts at Ti/Ga 2 O 3 interface is realized by tuning the conductivity of amorphous Ga 2 O 3 films with delicate control of oxygen flux in the sputtering process. The abundant donor-like oxygen vacancies distributed near the Ti/Ga 2 O 3 interface fascinate the tunneling process acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The only altered processing condition was the nitrogen flux, which was 0, 10, 40, and 120 sccm, and the resultant Ga 2 O 3 and GaON films are labeled as S0, S1, S2, and S3, respectively. According to our previous study, no obvious changes were observed in growth rate and the film thickness is about 125 nm for all samples . The RT-sputtered Ga 2 O 3 and GaON are in typical amorphous states, as evidenced by the characterization of the grazing incidence X-ray diffraction (GIXRD) spectra in Figure a, where no diffraction peaks related to Ga 2 O 3 are observed.…”
Section: Materials Preparation and Device Fabricationmentioning
confidence: 51%
See 2 more Smart Citations
“…The only altered processing condition was the nitrogen flux, which was 0, 10, 40, and 120 sccm, and the resultant Ga 2 O 3 and GaON films are labeled as S0, S1, S2, and S3, respectively. According to our previous study, no obvious changes were observed in growth rate and the film thickness is about 125 nm for all samples . The RT-sputtered Ga 2 O 3 and GaON are in typical amorphous states, as evidenced by the characterization of the grazing incidence X-ray diffraction (GIXRD) spectra in Figure a, where no diffraction peaks related to Ga 2 O 3 are observed.…”
Section: Materials Preparation and Device Fabricationmentioning
confidence: 51%
“…The amorphous Ga 2 O 3 detector (S0) exhibits a peak photoresponsivity of 10.35 A/W at the energy position of 4.95 eV with a sharp cutoff edge at 4.35 eV. The corresponding external quantum efficiency is as high as 5260%, which is a typical sign of a persistent photoconductivity effect mediated by a minority-carrier trapping effect as reported in most of Ga 2 O 3 PDs. With nitrogen incorporation, the photoresponse spectrum for sample S1 exhibits a remarkable reduction in photoresponsivity with an external quantum efficiency (EQE) of about 28%, which is a result of the suppression of the PPC trapping effect due to the reduction of V O and the increased recombination probability induced by nitrogen. A higher nitrogen composition in nitrogen-rich GaON leads toa quite low EQE (even less than 1%), which is resulted from the abundant recombination centers with subgap DOS near VBM .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…[ 29 ] Zhang et al reported the conversion of Ti/a‐Ga 2 O 3 contact from ohmic to Schottky by tuning the conductivity of a‐Ga 2 O 3 films with the help of a delicate control of oxygen flux during the sputtering process. [ 44 ] Kikuchi et al investigated the electrical and optical properties of a‐Ga 2 O 3 /Cu(In,Ga)Se 2 (CIGS) heterojunction photodiodes where gallium oxide layer is used as a hole‐blocking layer and buffer layer. The oxygen partial pressure during Ga 2 O 3 deposition was optimized to minimize the dark current.…”
Section: Preparation Methods Of A‐gaoxmentioning
confidence: 99%
“…Zhang et al demonstrated a conversion behavior from ohmic to Schottky contacts at Ti/Ga 2 O 3 interface by regulating the conductivity of a‐Ga 2 O 3 films with delicate control of oxygen flux in the RF‐sputtering process. [ 44 ] For a‐Ga 2 O 3 film deposited without oxygen, abundant donor‐like V O defects near the metal‐Ga 2 O 3 interface facilitated the tunneling process across the barrier, resulting in the contact conversion from Schottky to ohmic, which elevated the photocurrent and dark current simultaneously but degraded the light‐to‐dark ratio. On the contrary, Vu et al showed a different result with a‐Ga 2 O 3 film grown by PLD at 250 °C with a modulation of various oxygen partial pressures from 0 to 50 mTorr during the deposition process.…”
Section: Uv Pds Using A‐gaox Thin Filmsmentioning
confidence: 99%